2021
DOI: 10.7759/cureus.18841
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Its Potential Protective Role Against Inflammatory Bowel Disease: A Scoping Review

Abstract: Globally, around 15%-40% of patients suffering from inflammatory bowel disease (IBD) use Cannabis for pain reduction, increased appetite, and reduced need for other medications. Although many patients report having benefited by using Cannabis in IBD, there is still a lack of consensus regarding the use of Cannabis in IBD. The aim is to identify, explore and map literature on the potential protective role of Cannabis against IBD through this scoping review. Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Cannabinoid receptor stimulation attenuates murine colitis, while cannabinoid receptor antagonism and cannabinoid receptor deficient models reverse these anti-inflammatory effects [ 4 ]. Phytocannabinoids have been used in preclinical models of gastrointestinal inflammation [ 42 , 43 ] and several clinical trial have tested the efficacy of cannabinoid-based treatments in IBD patients [ 42 , 44 ]. Indeed, in our DSS murine colitis model, cannabinoid treatments improved the clinical condition of the mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoid receptor stimulation attenuates murine colitis, while cannabinoid receptor antagonism and cannabinoid receptor deficient models reverse these anti-inflammatory effects [ 4 ]. Phytocannabinoids have been used in preclinical models of gastrointestinal inflammation [ 42 , 43 ] and several clinical trial have tested the efficacy of cannabinoid-based treatments in IBD patients [ 42 , 44 ]. Indeed, in our DSS murine colitis model, cannabinoid treatments improved the clinical condition of the mice.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Although clinical studies are limited, cannabis has been shown to alleviate these symptoms in patients with IBD, improving their quality of life. 52–54 Chronic abdominal pain is among the most debilitating symptoms of IBD, and TRPV1 is known to modulate pain. 55 Recently, Defaye et al 56 proved that the inhibition of the visceral TRPV1 prevents microglial activation in the spinal cord and, subsequently, prevents persistent visceral hypersensitivity in colitis mice, suggesting that the channel could induce the transition from acute to chronic pain during active remission.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana is not a single-agent compound but a complex mixture of compounds in variable proportions, including terpenoids, cannabinoids, and flavonoids [6,7]. According to a study conducted on chronic marijuana users to determine chemical changes, 76.9% had transaminitis, 57.7% had hepatomegaly, 73.1% had splenomegaly, and 46.2% had hepatosplenomegaly [1].…”
Section: Discussionmentioning
confidence: 99%